2010
DOI: 10.1111/j.1469-7580.2010.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Implicit mechanistic role of the collagen, smooth muscle, and elastic tissue components in strengthening the air and blood capillaries of the avian lung

Abstract: To identify the forces that may exist in the parabronchus of the avian lung and that which may explain the reported strengths of the terminal respiratory units, the air capillaries and the blood capillaries, the arrangement of the parabronchial collagen fibers (CF) of the lung of the domestic fowl, Gallus gallus variant domesticus was investigated by discriminatory staining, selective alkali digestion, and vascular casting followed by alkali digestion. On the luminal circumference, the atrial and the infundibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
(125 reference statements)
1
21
0
Order By: Relevance
“…After comparing the strengths (stress tolerance) of the blood capillaries in the rabbit lungs, the dog lungs, and the horse lungs, Birks et al observed that stress failure may correlate with the thickness of the BGB (Birks et al, 1994), a property consistent with Laplace's relationship which states that wall stress is proportional to capillary radius but inversely proportional to wall thickness. We have demonstrated collagen fibers in the basement membrane of the BGB and the EECCs of the lung of the chicken (Maina et al, 2010) and immunolocalized type-IV collagen (Jimoh and Maina, 2013), a protein family of triple helical isoforms that form strong two-dimensional planar network of fibers (Timpl, 1989; Hudson et al, 1993; West, 2009), in the exchange tissue of the lung of the domestic fowl. The strength of the BGB of the mammalian lung has been attributed to presence of type-IV collagen in the basement membrane (Crouch et al, 1997; West and Mathieu-Costello, 1999; Maina and West, 2005; West, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…After comparing the strengths (stress tolerance) of the blood capillaries in the rabbit lungs, the dog lungs, and the horse lungs, Birks et al observed that stress failure may correlate with the thickness of the BGB (Birks et al, 1994), a property consistent with Laplace's relationship which states that wall stress is proportional to capillary radius but inversely proportional to wall thickness. We have demonstrated collagen fibers in the basement membrane of the BGB and the EECCs of the lung of the chicken (Maina et al, 2010) and immunolocalized type-IV collagen (Jimoh and Maina, 2013), a protein family of triple helical isoforms that form strong two-dimensional planar network of fibers (Timpl, 1989; Hudson et al, 1993; West, 2009), in the exchange tissue of the lung of the domestic fowl. The strength of the BGB of the mammalian lung has been attributed to presence of type-IV collagen in the basement membrane (Crouch et al, 1997; West and Mathieu-Costello, 1999; Maina and West, 2005; West, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by nature, we are working towards the goal of building a platform analogous to the natural lung, a modular gas exchange system that has a low footprint, high-selectivity, and requires little energy. [ 16 ] Many methods have been developed to create vascular structures in soft materials for self-healing materials, tissue-growth, and autonomic cooling. [ 31 ] We have recently demonstrated the synthesis of biomimetic gas exchange units capable of capturing CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…T-IVc is a distinctively high tensile strength, non-fibrillar, particularly molecularly well-organized form of collagen [22]. The T-IVc localized here in the BMs of the BGB and the E-ECCs, together with other possible forms of collagen, connects to the peripheral and the central parabronchial 'pillars' of CFs [13], with the gas ET being effectively 'suspended' between the 'columns'. A closely related family of proteins with similar amino acid sequences and similar chemical and physical properties [33], collagens, form 20 per cent of the total protein in mammals [34] and supporting cells [35].…”
Section: Discussionmentioning
confidence: 93%
“…Here, we noted that T-IVc exists within the relatively much thinner and less conspicuous BM of the E-ECCs and the epithelial cells connect periodically. The E-ECCs appear to form a part of an integrated support system of the avian lung [13], directly strengthening the ACs and indirectly strengthening the BCs. This study was funded by the National Research Foundation (NRF) of South Africa.…”
Section: Discussionmentioning
confidence: 99%